2009
DOI: 10.1186/1476-7120-7-16
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial volume measurement with automated border detection by 3-dimensional echocardiography: comparison with magnetic resonance imaging

Abstract: Objective: Left atrial size is an important marker for adverse cardiovascular events. There is general consensus that left atrial volume index (LAVI) is the best measurement of size. The current LAVI measurement techniques are laborious. Semi-automated measurement with a 3-dimensional echocardiography (3DE) system may be a practical clinical alternative to measure LAVI, but it has not been adequately evaluated against Magnetic Resonance Imaging (MRI) gold standard. The aim of this study was to compare the accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
95
1
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(113 citation statements)
references
References 16 publications
8
95
1
9
Order By: Relevance
“…Our data demonstrate very high correlations for LA max , LA min , LAEF, and LAEF true when compared to cardiac MRI. In line with previous studies comparing RT3DE assessment of the LA to MRI or CT, the present data demonstrate a consistent underestimation of RT3DE volumes [15,18].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Our data demonstrate very high correlations for LA max , LA min , LAEF, and LAEF true when compared to cardiac MRI. In line with previous studies comparing RT3DE assessment of the LA to MRI or CT, the present data demonstrate a consistent underestimation of RT3DE volumes [15,18].…”
Section: Discussionsupporting
confidence: 80%
“…In the present study, however, the differences were less pronounced than previously reported [15,18]. The higher spatial resolution of MRI in comparison to RT3DE has been repeatedly suggested as a likely explanation for the general underestimation of LA volumes by RT3DE along with a possible inclusion of pulmonary venous confluence or even part of the LA appendage into the actual LA volume when assessed by MRI.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…366,367 The advent of 3-D ECHO has improved the accuracy of ECHO volume measurements which correlate well with cardiac computed tomography 368,369 and magnetic resonance imaging. 370,371 Compared with 2D assessment of LA volume, 3DE also has superior prognostic prediction. 372,373 The recommended upper normal indexed LA volume is 34 mL/m 2 for both genders which fits well with a risk-based approach for determination of cut-off between a normal and an enlarged LA.…”
Section: Echocardiographymentioning
confidence: 99%
“…Until recently, however, 3D-TTE has had limited clinical applicability because of relatively laborious and time intensive acquisition and off-line processing [13][14] . The introduction of 'real time' 3D-TTE using matrix array transducers has resulted in sufficiently rapid image acquisition for clinical applications, but has not been rigorously validated 15 .…”
Section: Introductionmentioning
confidence: 99%